Muzyka w Dziennikach Stefana Kisielewskiego - Ciołkiewicz-Latek, Urszula (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2012)
The article points out the strands connected with music and the musical life in Poland in Dzienniki by Stefan Kisielewski. Kisielewski has been writing his Dzienniki between 1968 and 1980. There are numerous references to the composers, musicians and musicologists contemporary to Stefan Kisielewski with the author’s opinions on them and their works. Kisielewski presents often very sharp, uncompromising and scathing views about the people mentioned in his diary. The literary genre of diary is personal and not destined to be published though not devoid of the elements of the literary creation. This is why Kisielewski could express here his opinions freely, without the fear of a censorship. The pages of Stefan Kisielewski’s diary testified also to his anxiety about his own compositions’ artistic value. This is a fascinating evidence of his artistic process of composing and writing. The text underlines the fact that Dzienniki is a very illuminating book, with a great documentary and factual value. It gives a true picture of the difficult artistic life in PRL in the 60s and 70s, under the domination of the communist ideology. Simultaneously this is an invaluable record of Stefan Kisielewski’s complex and colourful personality. The article depicts also the changes in Kisielewski’s views on music and his own artistic activity as time goes by.